Factor H-related protein 1 promotes complement-mediated opsonization of Pseudomonas aeruginosa - González-Alsina, Alex; Martín-Merinero, Héctor; Mateu-Borrás, Margalida; Verd, María; Doménech-Sánchez, Antonio; Goldberg, Joanna B.; Rodríguez de Córdoba, Santiago; Albertí, Sebastián (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa is an important human opportunistic pathogen responsible for a wide range of infections. The complement system is the main early host defense mechanism to control these infections. P. aeruginosa counteracts complement attack by binding Factor H (FH), a complement regulator that inactivates C3b, preventing the formation of the C3-convertase and complement amplification on the bacterial surface. Factor H-related proteins (FHRs) are a group of plasma proteins evolutionarily related to FH that have been postulated to interfere in this bacterial mechanism of resisting complement.Here, we show that FHR-1 binds to P. aeruginosa via the outer membrane protein OprG in a lipopolysaccharide (LPS) O antigen-dependent manner. Binding assays with purified components or with FHR-1-deficient serum supplemented with FHR-1 show that FHR-1 competes with FH for binding to P. aeruginosa.Blockage of FH binding to C3b deposited on the bacteria reduces FH-mediated cofactor activity of C3b degradation, increasing the opsonization of the bacteria and the formation of the potent chemoattractant C5a.Overall, our findings indicate that FHR-1 is a host factor that promotes complement activation, facilitating clearance of P. aeruginosa by opsonophagocytosis.